Loss of the Arabidopsis Protein Kinases ANPs Affects Root Cell Wall Composition, and Triggers the Cell Wall Damage Syndrome - Gigli Bisceglia, Nora; Savatin, Daniel V.; Cervone, Felice; Engelsdorf, Timo; De Lorenzo, Giulia (Frontiers in Plant Science, 2018)
The Arabidopsis NPK1-related Protein kinases ANP1, ANP2 and ANP3 belong to the MAP kinase kinase kinase (MAPKKK) superfamily and were previously described to be crucial for cytokinesis, elicitor-induced immunity and development. Here we investigate the basis of their role in development by using conditional β-estradiol-inducible triple mutants to overcome lethality. In seedlings, lack of ANPs causes root cell bulging, with the transition zone being the most sensitive region. We uncover a role of ANPs in the regulation of cell wall composition and suggest that developmental defects of the triple mutants, observed at the cellular level, might be a consequence of the alterations of the pectic and cellulosic cell wall components. Lack of ANPs also induced a typical cell wall damage syndrome (CWDS) similar to that observed in plants treated with the cellulose biosynthesis inhibitor isoxaben (ISX). Moreover, anp double mutants and plants overexpressing single ANPs (ANP1 or ANP3) respectively showed increased and reduced accumulation of jasmonic acid and PDF1.2 transcripts upon ISX treatment, suggesting that ANPs are part of the pathway targeted by this inhibitor and play a role in cell wall integrity surveillance.